ACUTE MYOCARDIAL INFARCTION IN THE ABSENCE OF CORONARY ARTERY OBSTRUCTION - A COMPLICATION OF ANTICANCER THERAPY WITH CAPECITABINE - E. A. Kolomiets; I. A. Kurmukov; Sh. R. Kashiya; N. S. Besova; S. V. Limareva; A. P. Sandomirskaya (Столичная издательская компания, 2017)
The clinical case of acute myocardial infarction during a therapy with capecitabine is considered. Cardiovascular diseases and cardiovascular risk factors were not detected before the anticancer treatment. In a week after start of the fluoropyrimidine therapy, a routine electrocardiography revealed the acute phase of myocardial infarction of the lower localization. The diagnosis was confirmed by biochemical blood tests. The administration of capecitabine was discontinued. An urgent coronary angiography did not find obstruction of the coronary arteries. Thus, according to the results of a standard therapeutic examination of the patient, it was impossible to predict the development of capecitabine-induced cardiovascular toxicity before the start of anticancer therapy, as well as diagnose it clinically.